2020
DOI: 10.5433/1679-0359.2020v41n5p1705
|View full text |Cite
|
Sign up to set email alerts
|

Losses, chemical composition and aerobic stability of rye silage cv. Temprano subjected to different pre-flowering cuttings with or without fungicide

Abstract: Silages of rye harvested at the vegetative stage presented better fiber composition, lower lignification. Silages of rye harvested at the vegetative stage presented a less efficient fermentation process, lower concentration of organic acids and aerobic stability. The use of fungicide resulted in better dry matter content and fiber composition and improved the fermentation process generating lower DM losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Dry matter values were lower in the treatment with pyraclostrobin, probably because it has characteristics that increase water retention within the plant due to reduced stomatal opening (Grossmann et al, 1999). However, Heker et al (2020) and Silva et al (2022) report that the application of pyraclostrobin did not change the dry matter values of plants harvested at the vegetative stage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dry matter values were lower in the treatment with pyraclostrobin, probably because it has characteristics that increase water retention within the plant due to reduced stomatal opening (Grossmann et al, 1999). However, Heker et al (2020) and Silva et al (2022) report that the application of pyraclostrobin did not change the dry matter values of plants harvested at the vegetative stage.…”
Section: Discussionmentioning
confidence: 95%
“…Analyzing the treatment with pyraclostrobin on the ruminal disappearance rate of rye, at the preflowering stage, Heker et al (2020) observed an increase in values of soluble nutrients, from 26.8% to 28.7%, and maintenance of this difference at approximately 2 percentage points during the evaluation period of 0-48 hours of ruminal incubation.…”
Section: Discussionmentioning
confidence: 96%